Computational design of the helical hairpin structure of membrane-active antibacterial peptides based on RSV glycoprotein epitope scaffold. (April 2018) - Fu, Jinhua; Yang, Hong; Wang, Jing
Graphical abstract: Highlights: Membrane-active antibacterial peptides are derived from RSV glycoprotein epitope. Peptide–membrane interaction is investigated systematically using dynamics simulation. Peptide charge and conformation are critical for membrane activity and antibacterial potency. Abstract: Peptides with helical hairpin conformation have been found to possess potent membrane activity and can be exploited as the structural scaffold of antibacterial peptides (ABPs). Here, we attempted to computationally design membrane-active ABPs based on the helical hairpin motif of respiratory syncytial virus (RSV) glycoprotein epitope. Dynamics simulations revealed that the epitope peptide Rfe (net charge = −1) cannot effectively interact with and permeabilize bacterial membrane due to the electrostatic repulsion between the negatively charged peptide and anionic membrane surface. The native Rfe can be modified to a cationic peptide Rfe-KKK (net charge = +6) by triple mutation of its positively charged residues Glu256, Asp263 and Asp269 to a basic lysine as well as by C-terminal amidation. As might be expected, the modified peptide was able to target membrane surface with a moderate antibacterial potency (MIC = 50–100 μg/ml). Next, a cyclized version of the linear Rfe-KKK was generated, termed as cycRfe-KKK, which was observed to have improved membrane activity and increased antibacterial potency (MIC < 50 μg/ml) by pre-stabilizing amphipathic hairpin conformation of the peptide.